PENGAJARAN BAGI ANAK ANAK TENTANG PENGGUNAAN UANG DI KEHIDUPAN SEHARI HARI: DESA RANCA IYUH KEC. PANONGAN KAB. TANGERANG - Pujia, Dede Puspa; Kamela, Hurian; Susilowati, Susilowati; Widati, Sindik; Haryanto, Maharani Widie Anggraeni (LPPM Universitas Bina Bangsa, 2024)
The aims of implementing this Community Service are: 1) providing teaching about the proper and wise use of money, 2) providing teaching about the differences in fulfilling needs and desires related to the use of money. 3) Provide concrete evidence of cooperation between lecturers and students in meeting the community's needs for teaching the use of money in everyday life, which is very necessary. The implementation method is carried out using direct socialization, namely the process of visiting directly the place where the activity is carried out, namely Ranca Iyuh Village, Panongan District, Tangerang Regency, to provide teaching to children about the use of money in everyday life. The results of this activity are: 1) children can know the use of money in everyday life, 2) children can know the advantages of different uses of money based on needs and desires, 3) know and are skilled in setting aside money for savings